Inheritance of Different Religions from the Perspective of Shaykh Yusuf Al-Qaradhawi - Hutagaol, Khairul Hasbi; Purba, Zainal Arifin (JURNAL AKTA, 2023)
The provisions of inheritance in Islam are very clear, the provisions of the prohibition of inheritance between Muslims and non-Muslims have been agreed upon by classical jurists. The purpose of this study is to determine the Inheritance of Different Religions in the Perspective of Yusuf Al-Qaradhawi. This research uses descriptive analysis method. This type of research is qualitative then analysed normative juridical, namely by looking for the legal basis and regulations, by analysing the Supreme Court Decision Number 16K / AG / 2010, and Yusuf Al-Qardhawi's opinion in the book Fatwa Ma'ashira. problems that occur in families where the husband leaves an heir, namely a wife who is of a different religion from him, one of the obstacles for the heir to get his rights is due to different religious factors. The results of the study explain that according to Yusuf Al-Qaradhawi, inheritance of different religions can be given to heirs of different religions without the term mandatory will as has been determined by the Supreme Court decision Number: 16K / AG / 2010 related to the opinion of Yusuf Al-Qaradhawi about inheritance of different religions is supported by Ibn Taymiyyah.